PENINGKATAN KAPASITAS DAYA DUKUNG TANAH LEMPUNG DI CANGAR MELALUI STABILISASI DENGAN BATU KAPUR - Sutowijoyo, Hendro; Hadi, Dimas Setia (Fakultas Teknik, Universitas Wiraraja, 2025)
Subgrade soil is a crucial component of any construction project, be it roads, buildings, or bridges. Maintaining soil stability, particularly soil reinforcement, requires special attention. The clay soil at the Cangar site is fertile and located in the highlands. Laboratory soil testing is crucial for development planning in this area, as it enables the determination of soil properties and bearing capacity. To verify the maximum bearing capacity of the soil, a 20% limestone mixture was used, using the compaction modification and laboratory CBR testing methods. Test results revealed that the clay soil at the site has high plasticity. After mixing with limestone, the plasticity decreased by 11 points to level 15, classifying it as silty clay with moderate plasticity. Based on the CBR test of the original clay soil, the soil bearing capacity value was 22.4%, and after being mixed with 20% limestone, the value increased to 26.4%. In contrast, the maximum density of the original clay soil MDD was 0.99 grams/cm³; then, after being mixed with limestone, the MDD reached 1.24 grams/cm³. The distribution of grain size before being mixed with limestone was 2.02 grams of gravel, 61.03 grams of sand, and 436.95 grams of clay. After being given a limestone stabilizer, it was 37.06 grams of gravel, 123.45 grams of sand, and 339.49 grams of clay.